An immunoblotting procedure comprising O = 9, 12 and H = d antigens as an alternative to the Widal agglutination assay. Issue 11 (November 1998) - Chart, H; Ward, L R; Rowe, B
Abstract : AIMS: To compare the established Widal agglutination assay with an immunoblotting procedure. METHODS: 110 sera were used to compare the established Widal agglutination assay with an immunoblotting procedure incorporating lipopolysaccharide (LPS) (O = 9, 12) and flagellar (H = d) antigens. RESULTS: Antibodies to the LPS antigens were detected in 18 sera by the Widal assay and in 37 by immunoblotting. Antibodies to the flagellar antigens were detected in 27 sera by Widal assay and in 25 by immunoblotting. CONCLUSIONS: An immunoblotting procedure incorporating O = 9, 12 LPS and H = d flagellar antigens was rapid and more sensitive than the established Widal agglutination assay for providing evidence of infection with S typhi.